Oppositional movements in Egypt, from 1952 to Mubarak’s downfall - Puig Montana, Josep (Nómadas. Critical Journal of Social and Juridical Sciences, 2015)
Account of the main oppositional movements in Egypt, since Nasser’s rise to power until Mubarak’s downfall, considering both Islamist and secularist organizations and their relationship.